Clonal Relationship and Mutation Analysis in Lymphoplasmacytic Lymphoma/Waldenström Macroglobulinemia Associated With Diffuse Large B-cell Lymphoma - Madeleine R. Berendsen; Diede A.G. van Bladel; Eva Hesius; Cristina Berganza Irusquieta; Jos Rijntjes; Annemiek B. van Spriel; Ellen van der Spek; Johannes F.M. Pruijt; Leonie I. Kroeze; Konnie M. Hebeda; Sandra Croockewit; Wendy B.C. Stevens; et al. (HemaSphere, 2023)
Patients with lymphoplasmacytic lymphoma/Waldenström macroglobulinemia (LPL/WM) occasionally develop diffuse large B-cell lymphoma (DLBCL). This mostly results from LPL/WM transformation, although clonally unrelated DLBCL can also arise. LPL/WM is characterized by activating MYD88L265P (>95%) and CXCR4 mutations (~30%), but the genetic drivers of transformation remain to be identified. Here, in thirteen LPL/WM patients who developed DLBCL, the clonal relationship of LPL and DLBCL together with mutations contributing to transformation were investigated. In 2 LPL/WM patients (15%), high-throughput sequencing of immunoglobulin gene rearrangements showed evidence of >1 clonal B-cell population in LPL tissue biopsies. In the majority of LPL/WM patients, DLBCL presentations were clonally related to the dominant clone in LPL, providing evidence of transformation. However, in 3 patients (23%), DLBCL was clonally unrelated to the major malignant B-cell clone in LPL, of which 2 patients developed de novo DLBCL. In this study cohort, LPL displayed MYD88L265P mutation in 8 out of eleven patients analyzed (73%), while CXCR4 mutations were observed in 6 cases (55%). MYD88WT LPL biopsies present in 3 patients (27%) were characterized by CD79B and TNFAIP3 mutations. Upon transformation, DLBCL acquired novel mutations targeting BTG1, BTG2, CD79B, CARD11, TP53, and PIM1. Together, we demonstrate variable clonal B-cell dynamics in LPL/WM patients developing DLBCL, and the occurrence of clonally unrelated DLBCL in about one-quarter of LPL/WM patients. Moreover, we identified commonly mutated genes upon DLBCL transformation, which together with preserved mutations already present in LPL characterize the mutational landscape of DLBCL occurrences in LPL/WM patients.